Observation-Based Estimate of Net Community Production in Antarctic Sea Ice - Dalman, Laura A.; Meiners, Klaus M.; Thomas, David N.; Deman, Florian; Bestley, Sophie; Moreau, Sébastien; Arrigo, Kevin R.; Campbell, Karley; Corkill, Matthew; Cozzi, Stefano; Delille, Bruno; Fransson, Agneta; et al. (Geophysical Research Letters, 2025)
Abstract Antarctic sea ice is one of the largest biomes on Earth providing a critical habitat for ice algae. Measurements of primary production in Antarctic sea ice remain scarce and an observation-based estimate of primary production has not been revisited in over 30 years. We fill this knowledge gap by presenting a newly compiled circumpolar data set of particulate and dissolved organic carbon from 362 ice cores, sampled between 1989 and 2019, to estimate sea-ice net community production using a carbon biomass accumulation approach. Our estimate of 26.8?32.9 Tg C yr?1 accounts for at least 15%?18% of the total primary production in the Antarctic sea-ice zone, less than a previous observation-based estimate (63?70 Tg C yr?1) and consistent with recent modeled estimates. The results underpin the ecological significance of sea-ice algae as an early season resource for pelagic food webs.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; biogeokjemi; fotosyntese; havis alger; karbondioksid; karbonsyklus; oseanografi; primærproduksjon; sjøis

Southern Ocean Carbon Export Revealed by Backscatter and Oxygen Measurements From BGC-Argo Floats - Liniger, Guillaume; Moreau, Sébastien; Lannuzel, Delphine; Carranza, Magdalena M.; Strutton, Peter G. (Global Biogeochemical Cycles, 2025)
The Southern Ocean (south of 30°S) contributes significantly to global ocean carbon uptake through the solubility, physical and biological pumps. Many studies have estimated carbon export to the deep ocean, but very few have attempted a basin-scale perspective, or accounted for the sea-ice zone (SIZ). In this study, we use an extensive array of BGC-Argo floats to improve previous estimates of carbon export across basins and frontal zones, specifically including the SIZ. Using a new method involving changes in particulate organic carbon and dissolved oxygen along the mesopelagic layer, we find that the total Southern Ocean carbon export from 2014 to 2022 is 2.69 ± 1.23 PgC y?1. The polar Antarctic zone contributes the most (41%) with 1.09 ± 0.46 PgC y?1. Conversely, the SIZ contributes the least (8%) with 0.21 ± 0.09 PgC y?1 and displays a strong shallow respiration in the upper 200 m. However, the SIZ contribution can increase up to 14% depending on the depth range investigated. We also consider vertical turbulent fluxes, which can be neglected at depth but are important near the surface. Our work provides a complementary approach to previous studies and is relevant for work that focuses on evaluating the biogeochemical impacts of changes in Antarctic sea-ice extent. Refining estimates of carbon export and understanding its drivers ultimately impacts our comprehension of climate variability at the global ocean scale.
Publisher: John Wiley & Sons, Ltd Article number: e2024GB008193
Keywords: Sørishavet; biogeokjemi; fotosyntese; fytoplankton; havis; karbon syklus; sjøis

Response of Antarctic sea-ice algae to an experimental decrease in pH: a preliminary analysis from chlorophyll fluorescence imaging of melting ice - Castrisios, Katerina; Martin, Andrew; Müller, Marius N; Kennedy, Fraser; McMinn, Andrew; Ryan, Ken G (Polar Research, 2018)
Microorganisms confined to annual sea ice in the Southern Ocean are exposed to highly variable oxygen and carbonate chemistry dynamics because of the seasonal increase in biomass and limited exchange with the underlying water column. For sea-ice algae, physiological stress is likely to be exacerbated when the ice melts; however, variation in carbonate speciation has rarely been monitored during this important state-transition. Using pulse amplitude modulated fluorometry (Imaging-PAM, Walz), we documented in situ changes in the maximum quantum yield of photosystem II ( F v / F m ) of sea-ice algae melting out into seawater with initial pH values ranging from 7.66 to 6.39. Although the process of ice-melt elevated seawater pH by 0.2–0.55 units, we observed a decrease in F v / F m between 0.02 and 0.06 for each unit drop in pH during real-time fluorescence imaging. These results are considered preliminary but provide context for including carbonate chemistry monitoring in the design of future sea ice state-transition experiments. Imaging-PAM is a reliable technology for determining F v / F m , but is of limited use for obtaining additional photosynthetic parameters when imaging melting ice.
Keywords: Sørishavet; alger; fotosyntese; fysiologi; havis; karbonatkjemi; marin biologi; sjøis; økofysiologi

Algal biomass and pigments along a latitudinal gradient in Victoria Land lakes, East Antarctica - Borghini, Francesca; Colacevich, Andrea; Caruso, Tancredi; Bargagli, Roberto (Polar Research, 2016)
It is generally accepted that Antarctic terrestrial diversity decreases as latitude increases, but latitudinal patterns of several organisms are not always as clear as expected. The Victoria Land region is rich in lakes and ponds and spans 8 degrees of latitude that encompasses gradients in factors such as solar radiation, temperature, ice cover and day length. An understanding of the links between latitudinally driven environmental and biodiversity changes is essential to the understanding of the ecology and evolution of Antarctic biota and the formulation of hypotheses about likely future changes in biodiversity. As several studies have demonstrated that photosynthetic pigments are an excellent, although underused, tool for the study of lacustrine algal communities, the aim of the present study was to investigate variations in algal biomass and biodiversity across the latitudinal gradient of Victoria Land using sedimentary pigments. We test the hypothesis that the biodiversity of freshwater environments decreases as latitude increases. On the basis of our results, we propose using the number of sedimentary pigments as a proxy for algal diversity and the sum of chlorophyll a and bacteriochlorophyll a with their degradation derivatives as an index of biomass. Overall, our data show that biomass and diversity decrease as latitude increases but local environmental conditions, in particular, natural levels of eutrophy, can affect both productivity and diversity. Keywords: Biodiversity; photosynthetic pigments; proxy; continental Antarctica; sediments; biogeography.
Keywords: Antarktis; alger; biodiversitet; biogeografi; biomasse; ferskvann; fotosyntese; innsjø; sedimenter; økologi

Adjustment of pigment composition in Desmarestia (Desmarestiaceae) species along a sub-Antarctic to Antarctic latitudinal gradient - Mansilla, Andrés; Méndez, Fabio; Murcia, Silvia; Rodriguez, Juan Pablo; Marambio, Johanna; Rosenfeld, Sebastián; Yokoya, Nair; Bischof, Kai (Polar Research, 2016)
Photosynthesis at high latitudes demands efficient strategies of light utilization to maintain algal fitness and performance. The fitness, and physiological adaptation, of a plant or algae species depends in part on the abundance and efficiency of the pigments it can produce to utilize the light resource from its environment. We quantified pigment composition and concentration in six species of the brown macroalgal genus Desmarestia, collected from sub-Antarctic sites (Strait of Magellan, Beagle Channel–Cape Horn Province) and sites on the Antarctic Peninsula and adjacent islands. Sub-Antarctic Desmarestia species exhibited lower concentrations of chlorophyll a, chlorophyll c and fucoxanthin than endemic Antarctic species. Antarctic samples of D. menziesii and D. antarctica collected along a decreasing latitudinal gradient showed spatial and interspecific differences in light-harvesting pigment composition. Our results suggest distinct physiological adjustments in Desmarestia species in response to heterogeneous abiotic environmental conditions. The marine sub-Antarctic and Antarctic ecosystems are characterized by harsh environments (e.g., extreme irradiance, photoperiod, temperature, salinity) to which the physiology of macroalgal species must adapt. Keywords: Macroalgae; Phaeophyceae; photosynthesis; physiology; environmental heterogeneity; Chile.
Keywords: Antarktis; alger; fotosyntese; fysiologi; planter

Iron enrichment and photoreduction of iron under UV and PAR in the presence of hydroxycarboxylic acid: implications for phytoplankton growth in the Southern Ocean - Öztürk, Murat; Croot, Peter L.; Bertilsson, Stefan; Abrahamsson, Katarina; Karlson, Bengt; David, Roland; Fransson, Agneta; Sakshaug, Egil (The SWEDARP 1997/98 Expedition, 2004)
Iron(III) photoreduction and the responses of phytoplankton under ultraviolet (UV) and photosynthetically available radiation (PAR) were investigated with the presence of hydroxycarboxylic acid (glucaric acid (GA), a model compound for organic acids excreted by phytoplankton). The incubation experiments were carried out on board using seawater samples collected in the location of the winter ice edge (WIE) and the spring ice edge (SIE) of the Southern Ocean. In this paper, we focus on the results of experiment in WIE. Throughout the experiments, dissolved Fe(II), major nutrients and in vivo fluorescence were monitored regularly. In addition, Chl-a, POC/PON, cell densities of phytoplankton and bacteria, bacterial production, organic peroxide, hydrogen peroxide and total CO2 were measured. The results from the WIE show that iron enrichment had a substantial effect on phytoplankton growth rate. Fe(III) addition in the presence of GA (FeGA) gave higher Fe(II) concentration and higher growth rate of phytoplankton than those in controls. Our results suggest that hydroxycarboxylic acid had a significant chemical and biological impact. The presence of GA influenced iron photochemistry and iron availability to phytoplankton. Phytoplankton growth responses to iron enrichments in incubations under UV and PAR were completely dissimilar. It seems that FeGA addition prominently changes the harmful effect of UV on the phytoplankton population. This study provides preliminary information on how the photoreduction of iron(III) and the phytoplankton growth are affected by iron enrichment in the presence of hydroxycarboxylic acid.
Keywords: Sørishavet; biokjemi; fotosyntese; marin biologi; oseanografi; phytoplankton

Light rather than iron controls photosynthate production and allocation in Southern Ocean phytoplankton populations during austral autumn - van Oijen, Tim; van Leeuwe, Maria A.; Granum, E.; Weissing, Franz J.; Bellerby, Richard G. J.; Gieskes, W. W. C.; de Baar, Hein J. W. (Journal of Plankton Research, 2004)
The role of iron and light in controlling photosynthate production and allocation in phytoplankton populations of the Atlantic sector of the Southern Ocean was investigated in April–May 1999. The 14C incorporation into five biochemical pools (glucan, amino acids, proteins, lipids and polysaccharides) was measured during iron/light perturbation experiments. The diurnal Chl a-specific rates of carbon incorporation into these pools did not change in response to iron addition, yet were decreased at 20 μmol photons m−2 s−1, an irradiance comparable with the one at 20–45 m in situ depth. This suggests that the low phytoplankton biomass encountered (0.1–0.6 μg Chl a L−1) was mainly caused by light limitation in the deep wind mixed layer (>40 m). Regional differences in Chl a-specific carbon incorporation rates were not found in spite of differences in phytoplankton species composition: at the Antarctic Polar Front, biomass was dominated by a diatom population of Fragilariopsis kerguelensis, whereas smaller cells, including chrysophytes, were relatively more abundant in the Antarctic Circumpolar Current beyond the influence of frontal systems. Because mixing was often in excess of 100 m in the latter region, diatom cells may have been unable to fulfil their characteristically high Fe demand at low average light conditions, and thus became co-limited by both resources. Using a model that describes the 14C incorporation, the consistency was shown between the dynamics in the glucan pool in the field experiments and in laboratory experiments with an Antarctic diatom, Chaetoceros brevis. The glucan respiration rate was almost twice as high during the dark phase as during the light phase, which is consistent with the role of glucan as a reserve supplying energy and carbon skeletons for continued protein synthesis during the night.
Keywords: Sørishavet; biokjemi; fotosyntese; fytoplankton; marin biologi; oseanografi; planteplankton

Photosynthetic responses of selected Antarctic plants to solar radiation in the southern maritime Antarctic - Montiel, Pedro; Smith, Andrew; Keiller, Don (Polar Research, 1999)
The effects of UV-B exclusion and enhancement of solar radiation on photosynthesis of the two phanerogams which occur in the maritime Antarctic, Deschampsia antarctica and Colobanthus quitensis, and the moss Sanionia uncinats were investigated. Data on air temperature and solar radiation illustrate a drastic seasonal variation. Daily O3 column mean values and UV-B measured at ground level document the occurrence of the O3“hole” in the spring of 1997, with a concomitant increase in UV-B. The grass, D. antarctica, exhibited a broad temperature optimum for photosynthesis between 10–25°C while photosynthesis did not saturate even at high irradiance. The high water use efficiencies measured in the grass may be one of the features explaining the presence of this species in the maritime Antarctic. The net photosynthesis response to intercellular CO2 (A/ci) for D. antarctica was typical of a C3 plant. Exposure to a biologically effective UV-B irradiance of 0.74 W M-2 did not result in any significant change in either the maximum rate of photosynthesis at saturating CO2 and light, or in the initial carboxylation efficiency of Rubisco. (Vc,max). Furthermore while ambient (or enhanced) solar UV-B did not affect photochemical yield, measured in the field, of C. quitensis and D. antarctica, UV-B enhancement did affect negatively photochemical yield in S. uncinata. In D. antarctica plants, exposure to UV-B at low irradiances elicited increased flavonoid synthesis. The observed effects of UV-B enhancement on the moss (decreased photochemical yield) and the grass (increase in flavonoids) require further, separate investigation.
Keywords: Antarktis; botanikk; fotosyntese; klimaendringer; moser; planter

Effects of UV radiation on post-bloom phytoplankton populations in Kvalsund, North Norway - Walter Helbling, E.; Eilertsen, Hans Chr.; Villafañe, Virginia E.; Holm-Hansen, Osmund (Journal of Photochemistry and Photobiology B: Biology, 1996)
Our studies in the coastal waters in North Norway show that rates of photosynthesis of natural phytoplankton assemblages are strongly inhibited by solar UV radiation. When exposed to high irradiances of direct solar radiation, photosynthetic rates were increased by approximately 150% when all UV radiation was excluded from samples, with UVB radiation being responsible for approximately 50% of the total inhibition. There was no discernible threshold value for inhibition of photosynthesis by UV radiation, even at UV (280–400 nm) irradiances as low as 0.1 W m−2. When natural assemblages were incubated in situ, inhibition of photosynthetic rates were detectable down to 10 m, where solar irradiance was about 3% of the radiation incident on the sea surface. Based on the inhibition of photosynthetic rates at very low fluences of UV radiation, post-bloom assemblages of phytoplankton in North Norway and possibly also in the Arctic ocean appear to be more sensitive to solar UV radiation than phytoplankton from the Southern Ocean.
Keywords: Sørishavet; fotosyntese; fytoplankton; marin biologi; polarområdene; ultrafiolett stråling